Anticorrosive epoxy resin-based composite material and preparation method and application thereof
By adding bisphenol F, glutaric acid, flame retardant cross-linking agent and anti-UV cross-linking agent to the epoxy resin, and using the carboxylic acid cross-linking strategy, the problem of insufficient toughness, flame retardant performance and weather resistance of the epoxy resin is solved. problem, achieving improved mechanical properties and enhanced recyclability of materials.
Patent Information
- Application Number
- CN202411259907.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The existing epoxy resin has poor toughness and cannot be processed twice after curing and forming. Its flame retardant and weathering properties are also insufficient, which limits its use range.
Use bisphenol F epoxy resin, pentaic acid, flame -retardant cross -linked agent and UV -resistant diplomatic agent with carboxyl groups. The dynamic ester exchange of epoxy networks through carboxylic acid cross -linked strategies, enhance the mechanical properties of materials and recyclable materials sex.
Improve the mechanical performance, flame retardant performance and weather resistance of epoxy resin base composite materials, so that it has excellent anticorrosive performance and recyclable and recycling capabilities.
Smart Images

Figure CN118791709B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to an anti-corrosion epoxy resin-based composite material and a preparation method and application thereof. Background Art
[0002] Epoxy resin is a kind of high molecular polymer, specifically a general term for a class of polymers containing two or more epoxy groups in the molecule. Epoxy resin coating is a coating prepared with epoxy resin as the base material. Epoxy resin coating is widely used as the anti-corrosion layer of various plastic-coated steel pipes due to its excellent bonding properties, corrosion resistance, electrical insulation and thermal stability.
[0003] However, in the related art, epoxy resins are usually cured by amines. While the covalent cross-linking network brings advantages such as high modulus, high strength, and high heat resistance to epoxy resins, it also restricts the movement of its molecular chains, making the epoxy resins less tough and unable to be reprocessed after curing and molding. In addition, the flame retardant properties of unmodified epoxy resins are poor, and are HB grade according to the UL94 test standard. The high density of benzene rings in the cross-linking network makes the epoxy resins have poor weather resistance. These shortcomings severely limit the use of epoxy resins. Summary of the invention
[0004] In view of this, the present application provides an anti-corrosion epoxy resin-based composite material and a preparation method and application thereof.
[0005] The embodiment of the present application is implemented as follows: the embodiment of the present application provides an anti-corrosion epoxy resin-based composite material, comprising bisphenol F epoxy resin, glutaric acid, a flame retardant crosslinking agent and an anti-ultraviolet crosslinking agent; wherein the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent contain carboxyl groups;
[0006] The structural formula of the flame retardant crosslinking agent is shown below: ;
[0007] The structural formula of the anti-ultraviolet crosslinking agent is shown below: .
[0008] Optionally, in some embodiments of the present application, in the anti-corrosion epoxy resin-based composite material, the mass ratio of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent is (15~20): (2~4): (2.5~6.5): (2~3).
[0009] Optionally, in some embodiments of the present application, the anti-corrosion epoxy resin-based composite material further includes a catalyst; wherein,
[0010] The catalyst comprises N-methylimidazole; and / or
[0011] The mass ratio of the bisphenol F epoxy resin to the catalyst is (15-20): (0.8-1).
[0012] Accordingly, the present invention also provides a method for preparing an anti-corrosion epoxy resin-based composite material, comprising the following steps:
[0013] Provide bisphenol F epoxy resin, glutaric acid, a flame retardant crosslinking agent and an anti-ultraviolet crosslinking agent; wherein the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent contain carboxyl groups;
[0014] The structural formula of the flame retardant crosslinking agent is shown below: ;
[0015] The structural formula of the anti-ultraviolet crosslinking agent is shown below: ;
[0016] The bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent are mixed and reacted to obtain an anti-corrosion epoxy resin-based composite material.
[0017] Optionally, in some embodiments of the present application, the method for preparing the flame retardant crosslinking agent comprises:
[0018] Providing 3-hydroxypropionic acid and hexachlorocyclotriphosphazene;
[0019] The 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene are mixed and reacted to obtain a flame retardant crosslinking agent.
[0020] Optionally, in some embodiments of the present application, the mixing of the 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene comprises: providing a 3-hydroxypropionic acid dispersion and a hexachlorocyclotriphosphazene dispersion, wherein the 3-hydroxypropionic acid dispersion comprises the 3-hydroxypropionic acid and a first solvent, and the hexachlorocyclotriphosphazene dispersion comprises the hexachlorocyclotriphosphazene and a second solvent; mixing the 3-hydroxypropionic acid dispersion and the hexachlorocyclotriphosphazene dispersion; wherein,
[0021] The first solvent and the second solvent are each independently selected from one or more of ethyl acetate, tetrahydrofuran, chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, dimethyl sulfoxide, acetone, acetophenone, N,N-dimethylformamide, and pyrrole; and / or
[0022] In the 3-hydroxypropionic acid dispersion, the molar concentration of the 3-hydroxypropionic acid is 5 mol / L to 10 mol / L; and / or
[0023] In the hexachlorocyclotriphosphazene dispersion, the molar concentration of the hexachlorocyclotriphosphazene is 0.5 mol / L to 3 mol / L; and / or
[0024] The 3-hydroxypropionic acid dispersion also includes an acid binding agent; the acid binding agent is selected from one or more of triethylamine and pyridine; in the 3-hydroxypropionic acid dispersion, the molar ratio of the 3-hydroxypropionic acid to the acid binding agent is (5-10): (5-10); and / or
[0025] The molar ratio of the 3-hydroxypropionic acid to the hexachlorocyclotriphosphazene is (5-10): (0.5-3); and / or
[0026] The temperature for the reaction of the 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene is 25° C. to 40° C., and the reaction time is 2 h to 5 h.
[0027] Optionally, in some embodiments of the present application, the method for preparing the flame retardant crosslinking agent comprises:
[0028] Providing 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and succinic semialdehyde;
[0029] The 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde are mixed and reacted to obtain an anti-ultraviolet crosslinking agent.
[0030] Optionally, in some embodiments of the present application, the mixing of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde comprises: providing a 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion, wherein the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion comprises the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and a third solvent; mixing the succinic semialdehyde and the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion; wherein,
[0031] The third solvent is selected from one or more of benzene, toluene, chloroform, carbon tetrachloride, dichloromethane, dimethyl ether, tetraethylene glycol dimethyl ether, n-octane, isooctane, n-hexane, cyclohexane, and ethyl acetate; and / or
[0032] In the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion, the molar concentration of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is 0.3 mol / L to 0.6 mol / L; and / or
[0033] The molar ratio of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to the succinic semialdehyde is (0.3-0.6):(1-2); and / or
[0034] The reaction temperature of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde is 30° C. to 60° C., and the reaction time is 4 h to 8 h.
[0035] Optionally, in some embodiments of the present application, the mass ratio of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent is (15-20): (2-4): (2.5-6.5): (2-3); and / or
[0036] The mixture of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent further comprises adding a catalyst; the catalyst comprises N-methylimidazole; the mass ratio of the bisphenol F epoxy resin to the catalyst is (15-20): (0.8-1); and / or
[0037] The reaction temperature of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent is 100° C. to 160° C., and the reaction time is 4 h to 8 h.
[0038] Correspondingly, an embodiment of the present application also provides a plastic-coated steel pipe, which includes an anti-corrosion coating, and the material of the anti-corrosion coating includes any of the composite materials described above, or includes a composite material prepared by any of the above preparation methods.
[0039] The anti-corrosion epoxy resin-based composite material provided in the present application adopts a flame retardant and an anti-ultraviolet agent with multi-functional carboxyl groups to cure the epoxy resin. The epoxy groups undergo a ring-opening reaction with the carboxyl groups in the flame retardant cross-linking agent and the anti-ultraviolet agent to form ester groups. The toughening and recycling of the epoxy resin are achieved by promoting dynamic ester exchange within the epoxy network. The prepared epoxy resin-based composite material has excellent mechanical properties, flame retardant properties, and weather resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0041] Figure 1 This is a flow chart of a method for preparing an anti-corrosion epoxy resin-based composite material provided in an embodiment of the present application. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0043] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0044] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0045] In this application, "at least one" means one or more, and "plurality" means two or more. "One or several", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0046] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0047] The structural formula and molecular weight of some chemical reagents used in this application are described as follows:
[0048] Hexachlorocyclotriphosphazene: , molecular weight = 347.66;
[0049] 3-Hydroxypropionic acid: , molecular weight = 90.08;
[0050] 2,4,6-Tris(4-aminophenyl)-1,3,5-triazine: , molecular weight = 354.41;
[0051] Succinic Semialdehyde: , molecular weight = 102.09;
[0052] Glutaric acid: , molecular weight = 132.14;
[0053] N-Methylimidazole: , molecular weight = 82.11.
[0054] The technical solution of this application is as follows:
[0055] In a first aspect, an embodiment of the present application provides an anti-corrosion epoxy resin-based composite material, comprising bisphenol F epoxy resin, glutaric acid, a flame retardant crosslinking agent and an anti-ultraviolet crosslinking agent; wherein the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent contain carboxyl groups;
[0056] The structural formula of the flame retardant crosslinking agent is shown below: ;
[0057] The structural formula of the anti-ultraviolet crosslinking agent is shown below: .
[0058] It should be noted that bisphenol F epoxy resin, also known as bisphenol F diglycidyl ether, abbreviated as BPF resin, is a resin prepared by the reaction of phenol and formaldehyde under acidic catalysis to generate bisphenol F, and then undergoing a condensation reaction with epichlorohydrin in the presence of sodium hydroxide.
[0059] The anti-corrosion epoxy resin-based composite material provided in the present application adopts a flame retardant and an anti-ultraviolet agent with multi-functional carboxyl groups to cure the epoxy resin. The epoxy groups undergo a ring-opening reaction with the carboxyl groups in the flame retardant cross-linking agent and the anti-ultraviolet agent to form ester groups. The toughening and recycling of the epoxy resin are achieved by promoting dynamic ester exchange within the epoxy network. The prepared epoxy resin-based composite material has excellent mechanical properties, flame retardant properties, and weather resistance.
[0060] In some embodiments, in the anti-corrosion epoxy resin-based composite material, the mass ratio of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent is (15-20): (2-4): (2.5-6.5): (2-3), for example, it can be 16:3:3:2.5, 17:3:4:2.5, 18:2.5:5:2.8, 19:3:5.5:2, 17:2.8:3.5:3, etc. Within the mass ratio range, the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent can work together to improve the mechanical properties, flame retardant properties and weather resistance of the composite material.
[0061] In some embodiments, the anti-corrosion epoxy resin-based composite material further includes a catalyst.
[0062] Furthermore, the catalyst includes N-methylimidazole.
[0063] In some embodiments, the mass ratio of the bisphenol F epoxy resin to the catalyst is (15-20): (0.8-1), for example, 16:0.82, 17:0.85, 18:0.88, 19:0.9, 16:0.92, or any range between two ratios. Within the mass ratio range, the catalyst is beneficial to promote dynamic transesterification within the epoxy network to achieve toughening and recyclable reprocessing of the epoxy resin.
[0064] Second, see Figure 1 The present invention provides a method for preparing an anti-corrosion epoxy resin-based composite material, comprising the following steps:
[0065] S11, providing bisphenol F epoxy resin, glutaric acid, a flame retardant crosslinking agent and an anti-ultraviolet crosslinking agent; wherein the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent contain carboxyl groups;
[0066] The structural formula of the flame retardant crosslinking agent is shown below: ;
[0067] The structural formula of the anti-ultraviolet crosslinking agent is shown below: ;
[0068] S12, mixing the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent, and reacting them to obtain an anti-corrosion epoxy resin-based composite material.
[0069] The preparation method of the anti-corrosion epoxy resin-based composite material provided in the present application adopts a carboxylic acid cross-linking strategy, wherein the epoxy group and the carboxyl group undergo a ring-opening reaction to form an ester group, thereby promoting dynamic ester exchange within the epoxy network to achieve toughening and recycling of the epoxy resin; a flame retardant and an anti-ultraviolet agent with multi-functional carboxyl groups are used to cure the epoxy resin, and the prepared epoxy resin-based composite material has excellent mechanical properties, flame retardant properties, weather resistance and can be recycled and processed.
[0070] In the S11:
[0071] In some embodiments, the method for preparing the flame retardant crosslinking agent comprises:
[0072] S111, providing 3-hydroxypropionic acid and hexachlorocyclotriphosphazene;
[0073] S112, mixing the 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene, reacting to obtain a flame retardant crosslinking agent.
[0074] In some embodiments, the mixing of the 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene comprises: providing a 3-hydroxypropionic acid dispersion and a hexachlorocyclotriphosphazene dispersion, wherein the 3-hydroxypropionic acid dispersion comprises the 3-hydroxypropionic acid and a first solvent, and the hexachlorocyclotriphosphazene dispersion comprises the hexachlorocyclotriphosphazene and a second solvent; and mixing the 3-hydroxypropionic acid dispersion and the hexachlorocyclotriphosphazene dispersion.
[0075] In some embodiments, the first solvent and the second solvent are each independently selected from one or more of ethyl acetate, tetrahydrofuran, chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, dimethyl sulfoxide, acetone, acetophenone, N,N-dimethylformamide, and pyrrole.
[0076] In some embodiments, in the 3-hydroxypropionic acid dispersion, the molar concentration of the 3-hydroxypropionic acid is 5 mol / L to 10 mol / L, for example, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, or a range between any two values, etc. Within the molar concentration range, the 3-hydroxypropionic acid is facilitated to be uniformly dissolved and dispersed.
[0077] In some embodiments, in the hexachlorocyclotriphosphazene dispersion, the molar concentration of the hexachlorocyclotriphosphazene is 0.5 mol / L to 3 mol / L, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, or a range between any two values, etc. Within the molar concentration range, the hexachlorocyclotriphosphazene is facilitated to be uniformly dissolved and dispersed.
[0078] In some embodiments, the 3-hydroxypropionic acid dispersion further includes an acid binding agent.
[0079] In some embodiments, the acid binding agent is selected from one or more of triethylamine and pyridine.
[0080] In some embodiments, in the 3-hydroxypropionic acid dispersion, the molar ratio of the 3-hydroxypropionic acid to the acid binding agent is (5-10): (5-10), for example, 6:7, 7:6, 8:6, 9:7 or any range between two ratios, etc. Within the molar ratio range, the acid binding agent is beneficial to control and reduce the emission of acidic pollutants.
[0081] In some embodiments, the molar ratio of the 3-hydroxypropionic acid to the hexachlorocyclotriphosphazene is (5-10): (0.5-3), for example, 6:1, 7:2, 8:2.5, 9:1.5 or any range between two ratios, etc. Within the molar ratio range, it is beneficial for the 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene to fully react to generate a flame retardant crosslinking agent, thereby improving the product yield.
[0082] In some embodiments, the reaction temperature of the 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene is 25°C to 40°C, for example, 28°C, 30°C, 35°C, or any range between two values, etc.; the reaction time is 2h to 5h, for example, 2.5h, 3h, 3.5h, 4h, 4.5h, or any range between two values, etc. Thus, under the reaction conditions, the 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene are conducive to the efficient reaction to generate a flame retardant crosslinking agent.
[0083] In some embodiments, the reaction equation of the 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene is as shown below: .
[0084] In some embodiments, the method for preparing the flame retardant crosslinking agent comprises:
[0085] S113, providing 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and succinic semialdehyde;
[0086] S114, mixing the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde, and reacting them to obtain an anti-ultraviolet crosslinking agent.
[0087] In some embodiments, the mixing of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde comprises: providing a 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion, wherein the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion comprises the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and a third solvent; and mixing the succinic semialdehyde and the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion.
[0088] In some embodiments, the third solvent is selected from one or more of benzene, toluene, chloroform, carbon tetrachloride, dichloromethane, dimethyl ether, tetraethylene glycol dimethyl ether, n-octane, isooctane, n-hexane, cyclohexane, and ethyl acetate.
[0089] In some embodiments, in the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion, the molar concentration of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is 0.3 mol / L to 0.6 mol / L, for example, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L or a range between any two values, etc. Within the molar concentration range, the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is uniformly dissolved and dispersed.
[0090] In some embodiments, the molar ratio of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to the succinic semialdehyde is (0.3-0.6):(1-2), for example, 0.3:1, 0.35:1.5, 0.4:1.2, 0.5:1.8 or any range between two ratios. Within the molar ratio range, it is beneficial for the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde to fully react to generate an anti-ultraviolet crosslinking agent, thereby improving the product yield.
[0091] In some embodiments, the reaction temperature of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde is 30°C to 60°C, for example, 35°C, 40°C, 45°C, 50°C, 55°C, or any range between two values, etc.; the reaction time is 4h to 8h, for example, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, or any range between two values, etc. Thus, under the reaction conditions, it is conducive to the efficient reaction of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde to generate an anti-ultraviolet crosslinking agent.
[0092] In some embodiments, the reaction equation of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde is as shown below:
[0093] .
[0094] In S12:
[0095] In some embodiments, the mass ratio of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent is (15-20): (2-4): (2.5-6.5): (2-3), for example, it can be 16:3:3:2.5, 17:3:4:2.5, 18:2.5:5:2.8, 19:3:5.5:2, 17:2.8:3.5:3, etc. Within the mass ratio range, the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent can work together to improve the mechanical properties, flame retardant properties and weather resistance of the composite material.
[0096] In some embodiments, the mixing of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent, and the anti-ultraviolet crosslinking agent further comprises adding a catalyst.
[0097] Furthermore, the catalyst includes N-methylimidazole.
[0098] In some embodiments, the mass ratio of the bisphenol F epoxy resin to the catalyst is (15-20): (0.8-1), for example, 16:0.82, 17:0.85, 18:0.88, 19:0.9, 16:0.92, or any range between two ratios. Within the mass ratio range, the catalyst is beneficial to promote dynamic transesterification within the epoxy network to achieve toughening and recyclable reprocessing of the epoxy resin.
[0099] In some embodiments, the mixing of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent includes: mixing the glutaric acid, the flame retardant crosslinking agent, the anti-ultraviolet crosslinking agent with a fourth solvent to obtain a mixed liquid; mixing the bisphenol F epoxy resin with the mixed liquid.
[0100] In some embodiments, the fourth solvent is selected from one or more of ethyl acetate, tetrahydrofuran, chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, dimethyl sulfoxide, acetone, acetophenone, N,N-dimethylformamide, and pyrrole.
[0101] In some embodiments, the reaction temperature of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent is 100°C to 160°C, for example, 110°C, 120°C, 130°C, 140°C, 150°C or any range between two values, etc.; the reaction time is 4h to 8h, for example, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or any range between two values, etc. In this way, under the reaction conditions, it is conducive to the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent to fully and efficiently react to form a composite material.
[0102] In a third aspect, the present application also provides an application of the anti-corrosion epoxy resin-based composite material prepared by the above preparation method.
[0103] Specifically, a plastic-coated steel pipe includes an anti-corrosion coating, and the material of the anti-corrosion coating includes any of the composite materials described above, or includes a composite material prepared by any of the preparation methods described above.
[0104] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0105] Embodiment 1: This embodiment provides an anticorrosive epoxy resin-based composite material, and its preparation method is as follows:
[0106] Weigh 0.7 mol of 3-hydroxypropionic acid, 100 mL of ethyl acetate and 0.613 mol of acid-binding agent triethylamine into a 500 mL three-necked flask, start stirring to form a 3-hydroxypropionic acid dispersion; then dissolve 34.8 g of hexachlorocyclotriphosphazene in 100 mL of ethyl acetate in a beaker to form a hexachlorocyclotriphosphazene dispersion; gradually drip the hexachlorocyclotriphosphazene dispersion into the three-necked flask at 30°C, keep stirring, and stop the reaction after 4 hours; remove the ethyl acetate in the system by rotary evaporation, rinse with deionized water to remove the unreacted 3-hydroxypropionic acid and the generated triethylamine hydrochloride, and obtain a white powder product, which is a flame retardant crosslinking agent;
[0107] Weigh 0.1 mol of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 230 mL of toluene into a 500 mL three-necked flask, heat to 80°C, and stir until 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is completely dissolved; lower the reaction bath temperature to 50°C, add 0.35 mol of succinic semialdehyde into the three-necked flask, and react at 50°C for 6 hours; remove toluene in the system by rotary evaporation, and then rinse with ethanol to remove unreacted succinic semialdehyde to obtain a white powder product, which is an anti-ultraviolet crosslinking agent;
[0108] Take 17g of bisphenol F epoxy resin (BPF, brand NPEF170 / B, epoxy equivalent of 170, purchased from Shanghai Luohe Chemical Co., Ltd.) and add it to a 100mL beaker; take 4g of glutaric acid, 2.9g of flame retardant crosslinker, 2.9g of anti-ultraviolet crosslinker and 0.8g of catalyst N-methylimidazole and dissolve them in 20mL N,N-dimethylformamide (DMF) to form a mixed solution; then pour the mixed solution into the bisphenol F epoxy resin and stir it at room temperature to mix it evenly. Pour the obtained slurry into the mold and put it into a vacuum oven for curing and molding. Under vacuum conditions, cure it at 120℃ for 6 hours to obtain an anti-corrosion epoxy resin-based composite material.
[0109] Example 2: This example is basically the same as Example 1, except that the anti-corrosion epoxy resin-based composite material in this example contains 17 g of bisphenol F epoxy resin, 3.3 g of glutaric acid, 4 g of flame retardant crosslinker, 2.9 g of anti-ultraviolet crosslinker and 0.8 g of catalyst N-methylimidazole.
[0110] Example 3: This example is basically the same as Example 1, except that the anti-corrosion epoxy resin-based composite material in this example contains 17 g of bisphenol F epoxy resin, 2.6 g of glutaric acid, 5.1 g of flame retardant crosslinker, 2.9 g of anti-ultraviolet crosslinker and 0.8 g of catalyst N-methylimidazole.
[0111] Example 4: This example is basically the same as Example 1, except that the anti-corrosion epoxy resin-based composite material in this example contains 17 g of bisphenol F epoxy resin, 2 g of glutaric acid, 6.2 g of flame retardant crosslinking agent, 2.9 g of anti-ultraviolet crosslinking agent and 0.8 g of catalyst N-methylimidazole.
[0112] Comparative Example: This comparative example provides a composite material, and the preparation method is as follows:
[0113] Take 17g of bisphenol F epoxy resin (BPF, brand NPEF170 / B, epoxy equivalent of 170, purchased from Shanghai Luohe Chemical Co., Ltd.) and add it to a 100mL beaker. Then take 6.6g of glutaric acid, melt it completely at 120°C and pour it into the bisphenol F epoxy resin. After stirring evenly with a glass rod, pour the slurry into the mold and put it into a vacuum oven for curing. Under vacuum conditions, cure it at 12°C for 6 hours to obtain a composite material.
[0114] The anti-corrosion epoxy resin-based composite materials of Examples 1 to 4 and the composite materials of the comparative example were tested for mechanical properties (flexural modulus, notched impact), flame retardancy and corrosion resistance. The test results are shown in Table 1.
[0115] Among them, the bending modulus test is carried out in accordance with the standard ISO 178; the simply supported beam notched impact at 23°C is carried out in accordance with the standard ISO179; and the flame retardant performance test is carried out in accordance with the standard UL94. The method for the corrosion resistance test includes: pouring a quantitative epoxy resin slurry on the surface of the steel sheet, applying it evenly with a scraper, and then putting it into an oven to cure the epoxy resin according to the same process. The anti-corrosion performance test of epoxy resin is carried out in accordance with the standard GB / T10125-2012 "Artificial Atmosphere Corrosion Experiment Salt Spray Test" using acetic acid salt spray (AASS), the pH of the salt solution is controlled at 3.0~3.1, the pH value of the collected liquid in the salt spray box is 3.1~3.3, the test cycle is 240h, and the mass loss before and after the test is used to evaluate the corrosion resistance of the epoxy resin;
[0116] .
[0117] As shown in Table 1, the mechanical properties, flame retardant grades and anti-corrosion properties of the anti-corrosion epoxy resin-based composite materials provided in Examples 1 to 4 are far superior to those of the composite materials in the comparative examples; among them, the flexural modulus of Example 4 is the highest, which is 6.9 GPa; the notched impact strength of Example 2 is the highest, which is 7.9 KJ / m 2 ; The flame retardant grade of Example 3 and Example 4 is V-0, and has good flame retardant properties; the anti-corrosion performance of Example 2 and Example 4 is good, and the mass loss is only 1.1%.
[0118] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing an anticorrosive epoxy resin-based composite material, characterized in that: The steps include: Provide bisphenol F epoxy resin, glutaric acid, a flame retardant crosslinking agent and an anti-ultraviolet crosslinking agent; wherein the anti-ultraviolet crosslinking agent has a structural formula as shown below: ; The bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent are mixed and reacted to obtain an anti-corrosion epoxy resin-based composite material; The preparation method of the flame retardant crosslinking agent comprises: Providing 3-hydroxypropionic acid and hexachlorocyclotriphosphazene; The 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene are mixed and reacted to obtain a flame retardant crosslinking agent; The molar ratio of the 3-hydroxypropionic acid to the hexachlorocyclotriphosphazene is (5-10): (0.5-3); The temperature for the reaction of the 3-hydroxypropionic acid and the hexachlorocyclotriphosphazene is 25° C. to 40° C., and the reaction time is 2 h to 5 h.
2. The preparation method according to claim 1, characterized in that: The mixing of 3-hydroxypropionic acid and hexachlorocyclotriphosphazene comprises: providing a 3-hydroxypropionic acid dispersion and a hexachlorocyclotriphosphazene dispersion, wherein the 3-hydroxypropionic acid dispersion comprises the 3-hydroxypropionic acid and a first solvent, and the hexachlorocyclotriphosphazene dispersion comprises the hexachlorocyclotriphosphazene and a second solvent; mixing the 3-hydroxypropionic acid dispersion and the hexachlorocyclotriphosphazene dispersion; wherein, The first solvent and the second solvent are each independently selected from one or more of ethyl acetate, tetrahydrofuran, chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, dimethyl sulfoxide, acetone, acetophenone, N,N-dimethylformamide, and pyrrole; and / or In the 3-hydroxypropionic acid dispersion, the molar concentration of the 3-hydroxypropionic acid is 5 mol / L to 10 mol / L; and / or In the hexachlorocyclotriphosphazene dispersion, the molar concentration of the hexachlorocyclotriphosphazene is 0.5 mol / L to 3 mol / L; and / or The 3-hydroxypropionic acid dispersion also includes an acid binding agent; the acid binding agent is selected from one or more of triethylamine and pyridine; in the 3-hydroxypropionic acid dispersion, the molar ratio of the 3-hydroxypropionic acid to the acid binding agent is (5-10): (5-10).
3. The preparation method according to claim 1, characterized in that: The preparation method of the anti-ultraviolet crosslinking agent comprises: Providing 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and succinic semialdehyde; The 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde are mixed and reacted to obtain an anti-ultraviolet crosslinking agent.
4. The preparation method according to claim 3, characterized in that: The mixing of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and succinic semialdehyde comprises: providing a 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion, wherein the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion comprises the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and a third solvent; mixing the succinic semialdehyde and the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion; wherein, The third solvent is selected from one or more of benzene, toluene, chloroform, carbon tetrachloride, dichloromethane, dimethyl ether, tetraethylene glycol dimethyl ether, n-octane, isooctane, n-hexane, cyclohexane, and ethyl acetate; and / or In the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine dispersion, the molar concentration of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is 0.3 mol / L to 0.6 mol / L; and / or The molar ratio of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to the succinic semialdehyde is (0.3-0.6):(1-2); and / or The reaction temperature of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and the succinic semialdehyde is 30° C. to 60° C., and the reaction time is 4 h to 8 h.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent is (15-20): (2-4): (2.5-6.5): (2-3); and / or The mixture of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent further comprises adding a catalyst; the catalyst comprises N-methylimidazole; the mass ratio of the bisphenol F epoxy resin to the catalyst is (15-20): (0.8-1); and / or The reaction temperature of the bisphenol F epoxy resin, the glutaric acid, the flame retardant crosslinking agent and the anti-ultraviolet crosslinking agent is 100° C. to 160° C., and the reaction time is 4 h to 8 h.
6. An anticorrosive epoxy resin-based composite material, characterized in that: The anti-corrosion epoxy resin-based composite material is prepared by the preparation method according to any one of claims 1 to 5.
7. A plastic coated steel pipe, characterized in that: The plastic-coated steel pipe includes an anti-corrosion coating, and the material of the anti-corrosion coating includes the anti-corrosion epoxy resin-based composite material as described in claim 6, or includes the anti-corrosion epoxy resin-based composite material prepared by any preparation method as claimed in any one of claims 1 to 5.
Citation Information
Patent Citations
Low-smoke flame-retardant epoxy resin composite material and preparation method thereof
CN113881192A
Flame-retardant self-repairing waterborne polyurethane composite coating agent as well as preparation method and application thereof
CN114560983A